The Influence of the Elements of the Sarajevo "Film Festival" on Revisit and Recommendation Intention / Utjecaj elemenata "Sarajevo film festivala" na namjeru ponovne posjete i preporuke - Čaušević, Amra (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The purpose of the paper is to investigate the influence of the elements of satisfaction with the Sarajevo Film Festival on the intention of revisiting Sarajevo and the intention of recommending a visit to Sarajevo to others. The sample size for this research was 400 respondents - 200 foreign tourists who visited Sarajevo during the Sarajevo Film Festival and 200 tourists who came during the revious and the month following the event. Regression analysis was used to analyze and interpret the data obtained. The variables identified by the analysis as making a statistically significant contribution to explaining the revisit intention are: hospitality, relaxed atmosphere, service of the staff of the Sarajevo Film Festival, organization of the Festival, program and general experience at the Sarajevo Film Festival. The variables identified by the analysis as making a statistically significant contribution to explaining the intent of recommending to others are: general experience at SFF, organization of the festival, presence of (international and regional) celebrities, relaxed atmosphere, opportunity to make new acquaintances.